2022
DOI: 10.1001/jamanetworkopen.2022.26319
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Accessibility and Availability of Radiotherapy in Ghana

Abstract: ImportanceRadiotherapy is critical for comprehensive cancer care, but there are large gaps in access. Within Ghana, data on radiotherapy availability and on the relationship between distance and access are unknown.ObjectivesTo estimate the gaps in radiotherapy machine availability in Ghana and to describe the association between distance and access to care.Design, Setting, and ParticipantsThis is a cross-sectional, population-based study of radiotherapy delivery in Ghana in 2020 and model-based analysis of rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…However, radiotherapy continues to be unavailable or severely capacity limited in many low-resource countries where CC is endemic and restricted to the use of older treatment techniques that are associated with high recurrence rates and toxicity. 21 , 22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, radiotherapy continues to be unavailable or severely capacity limited in many low-resource countries where CC is endemic and restricted to the use of older treatment techniques that are associated with high recurrence rates and toxicity. 21 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…However, radiotherapy continues to be unavailable or severely capacity limited in many low-resource countries where CC is endemic and restricted to the use of older treatment techniques that are associated with high recurrence rates and toxicity. 21,22 This report outlines a staged approach to implementing advanced radiotherapy for CC at NCRNM, beginning with investment in a state-of-the-art CT simulator and IMRTcapable treatment machine followed by comprehensive training of a radiation oncologist in gynecological cancer radiation oncology at the PMH and continued collaboration between the NCRNM and PMH interdisciplinary teams afterward. It demonstrates the feasibility of using modern radiotherapy in a low-resource setting and provides early evidence of improved clinical outcomes compared with conventional treatment, specifically fewer acute side effects leading to improved treatment compliance.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of accessibility and availability of radiotherapy in Ghana found geographic disparities in accessibility with less than half of the population living within 100 km from a radiotherapy facility. 24 Given the known effects of radiation on complications, surgical outcomes, and PROs in mastectomy and post-mastectomy breast reconstruction, it is likely that higher rates of radiation in the Ghanaian cohort had negative consequences on quality-of-life experiences of these women. 25 Last, beyond these measured demographic and treatment differences between the cohorts, differences in community, culture, religion, and family dynamics between the populations of women could have had an effect on their experiences with mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Within Ghana, there are currently three radiation facilities in southern Ghana (two in Accra and one in Kumasi) serving the entire population. A recent study of accessibility and availability of radiotherapy in Ghana found geographic disparities in accessibility with less than half of the population living within 100 km from a radiotherapy facility 24 . Given the known effects of radiation on complications, surgical outcomes, and PROs in mastectomy and post-mastectomy breast reconstruction, it is likely that higher rates of radiation in the Ghanaian cohort had negative consequences on quality-of-life experiences of these women 25 .…”
Section: Discussionmentioning
confidence: 99%